Koto Baru Market as Efforts to Improve the Community Economy in X Koto District, Tanah Datar Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this study is to examine the Koto Baru Market as an effort to improve the economy of the community in X Koto sub-district, Tanah Datar Regency. Using descriptive research using qualitative methods, that is, providing an overview of research questions related to the potential of traditional markets to improve the community's economy. Koto baru Traditional market research uses this type of research because qualitative research usually examines the behavior and activities of an organization to obtain as much information as possible. About the possibility of traditional markets to improve the economy of the koto baru community which is the focus of research researchers. Then all information received in the field is collected in the form of words, such as words/behaviors and judgments, with the natural background of the person as an environment. This knowledge is then used to explain and describe the social phenomenon being studied. Qualitative methods are used to get deep data, some data contains meaning, meaning is actual data, solid data is something valuable behind visible data. Pasar Koto Baru is located in Kenagarian Koto Baru, X Koto District, Tanah Datar Regency which is very strategically located and very easy to reach because of easy road access. Pasar Koto Baru is a market that is included in the category of old markets because it was established in approximately 1895, the Koto Baru market which was originally very simple finally gradually changed until it became a traditional market. On this day the koto baru market has experienced a fairly rapid development The koto baru market operates on Mondays and Tuesdays, but at this time the koto baru market It has started operating on Sundays starting at noon ranging from 13.00 WIB to 18.00 WIB. The presence of the new koto market has sought to improve the community's economy, with the existence of this koto baru market people's income increases and social interaction of the community is increasing.